The Information Systems of Boarding House Search Application In Soegijapranata Catholic University Semarang Based On Android - Anastasia Widiastuti; Erdhi Widyarto Nugroho; Albertus Dwi Yoga Widiantoro (Journal of Business and Technology, 2021)
Soegijapranata Catholic University is one of the private universities that exist in Semarang. Many students from outside the region are on their education at this university. Students from outside the area seek for the temporary residence or domicile or are often referred to as boarding houses. The increasing of the development technology makes it easier for humans to find all the information. Boarding houses search application helps facilitate students in finding information about boarding houses which are desired. This application can be operated on Android and there are printed the profiles and the facilities of boarding houses, so that users can use them easily, and equipped with GPS to find boarding houses locations, it is not easier to find the locations of the boarding houses. From the results of this study, 90% agree with the existence of a boarding houses search application. This application is very beneficial for various parties such as boarding houses managers can promote their own boarding houses and students are easier to find boarding houses information which is desired and they can choose from the lowest price to the highest price.